POTENSI PERLINDUNGAN TERHADAP ILMU PENGETAHUAN DAN TEKNOLOGI OLEH DOSEN DI PERGURUAN TINGGI DALAM PENINGKATAN DAYA SAING GLOBAL - Sudjana, Sudjana (Yustitia, 2019)
This study discusses the potential of Intellectual Property protection on the creation of Science and Technology Development results by Lecturers in Higher Education and Intellectual Property Protection on the Creation of Science and Technology Development results in Universities in Improving Global Competitiveness.This study is a legal research using a normative juridical approach and descriptive analytical research specifications. The data used in this study are secondary data consisting of primary, secondary and tertiary legal materials. Data obtained through library studies and field research in the form of legislation, books, journals, and authoritative electronic media. The results of the study show that (1). the results of Science and Technology Development by university lecturers have the potential to obtain wealth protection in the field of Copyright and Patents, but do not rule out rights through other types of Intellectual Property. (2). Creation of Science and Technology development results that are protected by Intellectual Property and supported by the value chain and competitive scope will have high quality and reputation so as to enhance global competitiveness.